2020
DOI: 10.1038/s41598-020-68732-6
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of ferulic acid in topical gel formulation via nanoencapsulation and pH optimization

Abstract: Ferulic acid is a potent anti-oxidant with scientifically proven skin care efficacies. However, instability of this active in the skin care products restricted its wide application in beauty and skin care industries. This study aimed to stabilize ferulic acid in topical hydrogel formulation via nanoencapsulation technique. ferulic acid loaded nanocapsules were prepared via high pressure homogenization method and physicochemically characterized. Mean particle size of ferulic acid loaded nanocapsules was < 300 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…For this reason, one strategy that can be applied to overcome this limitation is the addition of preservatives in the formulation [12]. According to the product marketing materials of the samples analysed in this study, many antioxidant additives are added to the vitamin C serum, to improve the stability of the product [4], including vitamin E (α‐tocopherol), phloretin, ferulic acid, neohesperidin dihydrochalcone and tocopheryl acetate (Table 1). In addition, samples AH1, AH3 and CL2 present in their composition plant extracts with antioxidant characteristics [36–38], such as flavonoids of Ginkgo biloba leaf extract, pinus pinaster bark/bud extract and Salvia officinalis L. leaf extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, one strategy that can be applied to overcome this limitation is the addition of preservatives in the formulation [12]. According to the product marketing materials of the samples analysed in this study, many antioxidant additives are added to the vitamin C serum, to improve the stability of the product [4], including vitamin E (α‐tocopherol), phloretin, ferulic acid, neohesperidin dihydrochalcone and tocopheryl acetate (Table 1). In addition, samples AH1, AH3 and CL2 present in their composition plant extracts with antioxidant characteristics [36–38], such as flavonoids of Ginkgo biloba leaf extract, pinus pinaster bark/bud extract and Salvia officinalis L. leaf extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Skin is an external organ that is often exposed to environmental factors such as ultraviolet (UV) radiation, smoke and air pollution, which accelerate skin ageing [1]. A recommended technique to protect and treat the human skin against the action of these environmental aggressors is the topical administration of moisturizers [2] and facial serum [3] composed of antioxidants such as ferulic acid [4], L-ascorbic acid (L-AA, vitamin C) [3,5] or melatonin [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that almost half of the FA was destroyed in this period. Because FA is unstable under neutral/alkaline conditions, UVA depredates FA easily [ 14 , 21 ]. On maintaining the UVA irradiation up to 12 h later, the solution became stable and its RR value held at 29.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The neutral pH value indicates that the niosomal gel of OZ can avoid any possible skin irritation rendering the niosomal formulation to be safe. Furthermore, pH optimization can also improve the stabilization of active pharmaceutical ingredients in gel formulation for topical use (Das and Wong 2020). The torque obtained was more than 85%.…”
Section: Characterization (Ph Measurement Viscosity and Draize Test) Of Oz Niosomal Gelmentioning
confidence: 99%